Genetic Diversity of Phytophthora colocasiae Causing Taro Leaf Blight: Analysis Using Start Codon Targeted (SCoT) Polymorphism - Nath, Vishnu Sukumari; Hegde, Vinayaka Mahabaleswar; Jeeva, Muthulekshmi Lajapathy; Misra, Raj Shekar; Veena, Syamala Swayamvaran; Raj, Mithun; Nair, Sree Sankar Dharveekaran (JOURNAL OF ROOT CROPS, 2015)
The Oomycetous fungus Phytophthora colocasiae that causes taro leaf blight is one of the most devastating diseases of taro and is widely distributed in India. Cultural and molecular techniques were employed for assessing the genetic variability among 30 isolates of P. colocasiae obtained from different geographical origins of India. Cultural characters like pathogenicity assay, mating type and metalaxyl sensitivity showed variation among isolates. Eight Start Codon Targeted Polymorphism (SCoT) markers produced 121 reproducible fragments with 100% polymorphism. The average value of the number of observed alleles, the number of effective alleles, mean Neiâ€™s genetic diversity, and Shannonâ€™s information index were 2.00 ± 0.00, 1.58 ± 0.30, 0.34 ± 0.13, and 0.51 ± 0.16, respectively. Analysis of molecular variance (AMOVA) showed that 89 % of the diversity was present within population of P. colocasiae. Dendrograms based on the molecular data using the unweighted pair group method with arithmetic mean (UPGMA) classified the P. colocasiae isolates into two major clusters. Cophenetic correlation coefficient between dendrogram and original similarity matrix were significant for SCoT marker (r = 0.904). The results of this study displayed a high level of genetic variation among the isolates irrespective of the geographical origin. The possible mechanisms and implications of this genetic variation are discussed.